(untitled) (Metakognisi, 2025)
Lexicon is a collection or list of words in a language, along with information about their meaning, form, and use. Lexicon can be interpreted as a dictionary or vocabulary used in a particular language, which functionsto provide n understanding of the meaning of word, grammatical forms, and relationships between words. The objectives of this study are (1) to describe the form of lexicon naming Sundanese traditional marriage traditions in Bayah District, (2) to describe the meaning of lexicon naming Sundanese traditional marriage traditions in Bayah District, and (3) to explain the implications of the findings of lexicon naming Sundanese traditional marriage traditions in Bayah District for local content learning in junior high schools. This study uses a qualitative descriptive analysis method with the determinant element separation (PUP) analysis technique. The results of the study showed that 21 lexicons and meanings of the culture of marriage traditions were found. There were 2 lexicons of marriage traditions that were included in monomorphemic word, including the Ngala and Sungkem lexicons. Lexicons that include polymorphemic words were found to be 7, including the lexicons Neunden Omong, Buka Pintu, Nincak Endog, Meupeuskeun Kendi, and Patarik-tarik Bakakak. Lexicons that include nominal phrases were found to be 7, including the lexicons Seren Sumeren, Khutbah Nikah, Akad Nikah, Sawer Panganten Meuleum Harupat, Huap Lingkung, and Huap Pamungkas. The cultural meanings contained in these lexicons were obtained through transcriptions of interviews with informants who master the tradition. These findings not only enrich the understanding of Sundanese traditional marriage traditions, but also provide an important contribution to the learning of local contenct in junior high schools as an effort to preserve culture.